Southern African agriculture and climate change: A comprehensive analysis - Zimbabwe - Mugabe, Francis T.; Hachigonta, Sepo; Sibanda, Lindiwe M.; Thomas, Timothy S. (International Food Policy Research Institute, 2012)
This summary note is an excerpt from the chapter on Zimbabwe that will appear in the peer-reviewed IFPRI monograph, Southern African Agriculture and Climate Change: A Comprehensive Analysis.